Study of the association between the BMP4 gene and congenital anomalies of the kidney and urinary tract - Geisilaine Soares dos Reis; Ana Cristina Simoes e Silva; Izabella Silva Freitas; Thiago Ramos Heilbuth; Luiz Armando de Marco; Eduardo Araujo Oliveira; Debora Marques Miranda (Elsevier, 2014)
OBJECTIVE: To determine the frequency of different phenotypes for congenital anomalies of the kidney and urinary tract (CAKUT) in a Brazilian sample, and to evaluate the association between the CAKUT phenotypes and the BMP4 gene. METHODS: In this study, 457 Brazilian individuals were analyzed in an attempt to establish the association between the BMP4 gene and the CAKUT diagnosis. A case-control sample was genotyped for three BMP4 gene polymorphisms. RESULTS: Association data was established with CAKUT sample as a whole and with the three most important CAKUT phenotypes: multicystic dysplastic kidney disease (MDK), ureteropelvic junction obstruction (UPJO) and vesicoureteral reflux (VUR). When the sample was segregated in these three phenotypes, associations between the BMP4 gene were observed with UPJO and with MDK. Conversely, VUR was not associated to the polymorphisms of the BMP4 gene. CONCLUSIONS: The present data suggest that Brazilian individuals with polymorphisms of the BMP4 gene have a higher risk to develop CAKUT, especially the malformations related to nephrogenesis and initial branching such as MDK and UPJO. Conversely, VUR appeared not to be related to BMP4 gene.